ADAPT technique with ACE68 and ACE64 reperfusion catheters in ischemic stroke treatment: results from the PROMISE study. (30th July 2018) - Schramm, Peter; Navia, Pedro; Papa, Rosario; Zamarro, Joaquin; Tomasello, Alejandro; Weber, Werner; Fiehler, Jens; Michel, Patrik; Pereira, Vitor M; Krings, Timo; Gralla, Jan; Santalucia, Paola; et al.
Abstract : Background and purpose: The recent randomized trials demonstrated the benefit of mechanical thrombectomy in stroke therapy. However, treatment using different strategies is an ongoing area of investigation. The PROMISE study analyzed the safety and effectiveness of the Penumbra System with the ACE68 and ACE64 reperfusion catheters in aspiration thrombectomy of stroke, using A Direct Aspiration First Pass Technique (ADAPT). Methods: PROMISE was a prospective study which enrolled 204 patients with intracranial anterior circulation large vessel occlusion (LVO) ischemic stroke in 20 centers from February 2016 to May 2017. Initial treatment was with the ACE68/ACE64 catheters within 6 hours of symptom onset. Imaging and safety review was performed by an independent Core Laboratory and a Clinical Events Committee. The primary angiographic outcome was revascularization to mTICI 2b-3 at immediate post-procedure and the primary clinical outcome was 90-day modified Rankin Scale (mRS) score ≤2. Safety assessment included device- and procedure-related serious adverse events (SAEs), symptomatic intracranial hemorrhage (sICH), mortality, and embolization of new territory (ENT). Results: Enrolled patients had a median age of 74 (IQR 65–80) years and a median admission NIHSS of 16 (IQR 11–20). The post-procedure mTICI 2b-3 revascularization rate was 93.1% and the 90-day mRS 0–2 rate was 61%. Device- and procedure-related SAEs at 24 hours occurred in 1.5% and 3.4%, respectively, 90-day mortality was 7.5%, sICH occurred in 2.9% while ENT occurred in 1.5%. Conclusions: For frontline therapy of LVO stroke, the ACE68/ACE64 catheters for aspiration thrombectomy were found to be safe and showed similar efficacy to randomized trials using other revascularization techniques. Clinical Trial Registration: NCT02678169 ; Pre-results.